IMPLEMENTASI SMART HYDROPONIK DI DESA CIBIRU WETAN UNTUK PENINGKATAN PEREKONOMIAN MASYARAKAT - Rosmiati, Mia; M. Mandasari, Rizza Indah; Brotoharsono, Tri; Fakhri, Humam Ibadillah; Pratama, Luthfi Revansyah (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Cibiru Wetan Village is one of the areas located in the eastern part of Bandung Regency. This village has an area of ​​325 hectares and has a population of 17,071 people. One of the activities of Cibiru Wetan Village that supports the economic activities of the community is the food security system carried out by the Women Farmers Group (KWT). The economic activities carried out by KWT include managing agricultural land that produces vegetables and fruits that can be sold to the community or to the market. Agricultural activities carried out by KWT are still conventional in nature by utilizing existing open land so that the amount of vegetable or fruit production produced is still limited, therefore through the construction of Greenhouses and the development of smart hydroponics can be one solution in increasing the volume of vegetable production. Smart hydroponics is built by integrating a wireless sensor network with an interface display using an android application. This system uses an Arduino Uno as a microcontroller, a TDS sensor that functions to read dissolved nutrients, a water flow sensor to regulate the speed of water flow and a DHT 22 which will be used to measure the temperature of the nutrient solution. Meanwhile, for the interface display using an android application built using the Kotlin framework. Based on the test results, this system has an accurate sensor reading accuracy value with an accuracy value above 90%.